Implementasi ASEAN Tourism Strategic Plan (ATSP) dalam Pengembangan Pariwisata Sumatra Barat - Moenir, Haiyyu Darman; Halim, Abdul; Maharani, Ajeng Masna Rifamida (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
Tourism in the ASEAN context is considered substantial in supporting the economic growth acceleration in each ASEAN country. Therefore, ASEAN has formed a joint strategy to support tourism development in each ASEAN member country through the formation of the ATSP (ASEAN Tourism Strategic Plan). Indonesia is one of the ASEAN member countries also has focus on the tourism sector. One of the provinces with good tourism opportunities in Indonesia is West Sumatra. This study will analyze how West Sumatra maximizes tourism potential through the implementation of ATSP. The method chosen to explain and analyze the problem in this research is a qualitative method with a descriptive-analytic type of research. Through a qualitative approach allows researchers to be able to produce a detailed description of the policies taken by the Government of West Sumatra within the framework of the ATSP for regional tourism development. The findings of this study indicate that the government of West Sumatra has not yet maximized the potential of the region in the tourism sector and has not implemented ATSP thoroughly.